Wounds of the past, screens of the present: how childhood adversities shape social media behaviours in adulthood - Cristina Elisa Orso (Review of Economics of the Household, 2025)
This paper explores whether individuals that grew up in adverse environments are more likely to engage in harmful use of social media later in life. We rely on the first EU-wide, individual-level survey that comprises information on social media usage time, patterns, motivations, and potential overuse, together with a rich set of socio-economic conditions, experiences of loneliness, and traumatic events in childhood of individuals residing in 27 European member states. We find that the presence of close relatives with severe drinking and mental health problems during childhood is positively associated with excessive use of social media in adulthood. Adverse childhood environments have a significant impact on passive overuse of digital platforms, leading to increased neglect of work and family responsibilities. The results also indicate interesting geographical patterns as well as gender and cohort effects, with younger male individuals and those living in Northern and Eastern European countries being particularly affected. Finally, we show that the childhood environment spillovers are, to some extent, mediated by loneliness and social isolation in adulthood. Our findings have significant policy implications since the interplay between the excessive social media use and adverse childhood experiences may jointly undermine individuals' well-being and cognitive development, representing a pressing public health issue.
Keywords: L82; D91; I12; I31; H4; 330; Adverse childhood conditions; social media overuse; neglect; loneliness; social isolation